Corporate Control around the World - AMINADAV, GUR; PAPAIOANNOU, ELIAS (Journal of Finance, 2020)
ABSTRACT We study corporate control tracing controlling shareholders for thousands of listed firms from 127 countries over 2004 to 2012. Government and family control is pervasive in civil‐law countries. Blocks are commonplace, but less so in common‐law countries. These patterns apply to large, medium, and small firms. In contrast, the development‐control nexus is heterogeneous; strong for large but absent for small firms. Control correlates strongly with shareholder protection, the stringency of employment contracts and unions power. Conversely, the correlations with creditor rights, legal formalism, and entry regulation appear weak. These patterns support both legal origin and political theories of financial development.